2022
DOI: 10.3390/healthcare10010103
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Vision in the Relationship between Proprioception and Postural Control in Older Adults, as Compared to Teenagers and Younger and Middle-Aged Adults

Abstract: The aim of this study is to analyze the mediating role of vision in the relationship between conscious lower limb proprioception (dominant knee) and bipedal postural control (with eyes open and closed) in older adults, as compared with teenagers, younger adults and middle-aged adults. Methods: The sample consisted of 119 healthy, physically active participants. Postural control was assessed using the bipedal Romberg test with participants’ eyes open and closed on a force platform. Proprioception was measured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…1,3 Postural stability depends on the central integration of 3 crucial sensory components: the visual, vestibular, and somatosensory (proprioceptive, cutaneous, and joint) systems and their rapid inputs for information processing. [1][2][3][4] Apart from the sensory organization mechanism in which the central nervous system integrates the visual, vestibular, and somatosensory inputs, a motor tuning process, which necessitates the synchronization of musculoskeletal reflexes, and an internal representation of positions of body parts in space are required for successful postural control. 1,2 These mechanisms work thoroughly to maintain a specific static state (eg, upright stance) or dynamic circumstance (eg, walking), as well as compensate for body perturbations to prevent falls.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 Postural stability depends on the central integration of 3 crucial sensory components: the visual, vestibular, and somatosensory (proprioceptive, cutaneous, and joint) systems and their rapid inputs for information processing. [1][2][3][4] Apart from the sensory organization mechanism in which the central nervous system integrates the visual, vestibular, and somatosensory inputs, a motor tuning process, which necessitates the synchronization of musculoskeletal reflexes, and an internal representation of positions of body parts in space are required for successful postural control. 1,2 These mechanisms work thoroughly to maintain a specific static state (eg, upright stance) or dynamic circumstance (eg, walking), as well as compensate for body perturbations to prevent falls.…”
Section: To the Editormentioning
confidence: 99%
“…1 The predominant role of vision in postural control has been confirmed by the findings of significant increases in postural instability in eyes-closed situations compared to eyes-open situations. 3,4 Normal vision is critical in developing and maintaining balance control. 1,3 When normal binocular vision is disrupted in childhood, especially by strabismus and/or amblyopia, balance is also affected.…”
Section: To the Editormentioning
confidence: 99%
“…Clinical examination in these patients can include quantitative sensory testing (QST) to asses this sensory stimulus and also provide the advantage of directly assessing the degree of sensory loss in the foot. Some of the more commonly used techniques are “Semmes-Weinstein monofilaments”, ‘’thermal and cooling threshold‘’, “perception of vibration”, and “computer-assisted sensory examination”[ 21 - 23 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Several studies have compared the performance between young adults and the elderly in dual‐task situations to evaluate the role of aging in integrating visual information for postural control. Despite an overall increase in postural sway with aging, these dual‐task studies have shown that the visual contribution to postural control remains relatively unaffected by age 15,16 . Furthermore, the effects of distance and gaze position on postural stability have been investigated by measuring the motion of the center of pressure (CoP) by Kapoula et al 17 Their findings suggest that a narrow range of CoP displacements is associated with decreased velocity and range of body oscillation in both anterior‐posterior and medial‐lateral directions, regardless of age, at short distances.…”
Section: Introductionmentioning
confidence: 99%